Improving the anti-fouling property and permeate flux of hollow fiber composite nanofiltration membrane using β-cyclodextrin - He, Yuantao; Miao, Jing; Jiang, Zhibin; Tu, Kai; Yang, Hao; Chen, Shunquan; Zhang, Ling; Zhang, Rui (Scientific reports, 2019)
Hollow fiber composite NF membranes with improved anti-fouling property and water flux were prepared via interfacial polymerizationand layer-by-layer method using polyethylenimine (PEI), isophthaloyl dichloride (IPC), and β-cyclodextrin (β-CD). The chemical structures and the morphologies of the resultant NF membranes were characterized by attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy and scanning electron microscopy (SEM). The effects of β-CD concentration on membrane morphologies, nanofiltration performances, surface hydrophilicities and anti-fouling properties were investigated. It was found that the permeate flux increased with increasing the β-CD concentration, and no decline of rejection was observed. The results showed that the introduction of β-CD improved surface hydrophilicities and anti-fouling performances of composite hollow fiber NF membranes. The water contact angles decreased from 61.3° to 23° within creasing the concentration of β-CD from 0 to 2.0 wt.%. The resultant hollow fiber composite NF membrane showed an excellent anti-fouling property with the flux recovery ratio of 97.6%, which was much better than that of the original polyamide (PA) NF membranes.